CSR and employee outcomes: a systematic literature review - Yasser Yassin; Markus Beckmann (Management Review Quarterly, 2024)
The purpose of this research is to consolidate and extend the current literature on employee outcomes of CSR (referred to as micro-level outcomes). The authors use a systematic review of the literature as a method to summarize and synthesise the different effects of CSR activities on employees based on 270 journal articles. The contribution of this paper is that it provides a comprehensive list of employee outcomes classified into different categories and a conceptual framework that maps desirable and undesirable outcomes of CSR activities on employees. The results show that various dimensions of CSR have different effects on employee outcomes. In addition, we explain mediators of CSR-employee outcomes relationships and moderators that could strengthen or weaken this relationship. The review reveals important gaps and offers a research agenda for the future. We have found only a few studies dealing with the negative impacts of CSR on employees as well as only a few studies that explain how different dimensions of CSR affect employees differently. The study has also practical implications for companies, as understanding different effects of CSR on employees helps organizations to design and implement CSR strategies and policies that foster employees' positive attitudes and behaviours as well as prevent or reduce the negative effects, and hence create a business value and sustainable growth for the company.
Keywords: 650; Corporate social responsibility; Micro-level; Employee outcomes; Employee attitudes; Employee behaviours; Employee well-being; Systematic review